Effect of Work Environment, Reward, Punishment and Work Discipline on Organizational Commitment (Study on Employees of the Regional Financial Management Agency of Tambrauw Regency, West Papua Province) - Ratu Mambrasar; Victor Lengkong; Rita Taroreh (Research Parks Publishers, 2021)
This study aims to analyze the effect of the work environment, reward, punishment and work discipline on organizational commitmentto employees of the Regional Financial Management Agency Office of Tambrauw Regency, West Papua Province in 2020.This research is associative. The research method used is a survey method through the provision of questionnaires. The population in the study amounted to 43 respondents consisting of all employees of the Regional Financial Management Agency Office of Tambrauw Regency, Papua Province. The number of samples in this study amounted to 37 people. The sampling technique used is census. Based on the results of research analyzed through multiple linear regression, work environment (X1), reward (X2), punishment (X4) and work discipline (X4) have a simultaneous effect on organizational commitment. While partially, the work environment (X1), reward (X2), and punishment (X4) have a positive and insignificant effect on organizational commitment, and the work discipline variable (X4) has a positive and significant effect on organizational commitment. employees of the Regional Financial Management Agency Office of Tambrauw Regency, West Papua Province in 2020.